Research on the impact of the digital economy on carbon emissions based on the dual perspectives of carbon emission reduction and carbon efficiency - Xin Liu; Liang Chen; Yifu Lu; Ming Chang; Yi Xiao; Haonan Yang; Deyuan Kong; Lili Zhang (Scientific Reports)
Abstract China’s digital economy is currently thriving, with the “dual carbon” targets representing a significant pursuit of economic development. The role of the digital economy in achieving these targets warrants detailed discussion. Using urban panel data from China spanning 2011 to 2021, this paper empirically examines the impact of the digital economy on urban carbon emissions. The findings reveal several key points: Firstly, the digital economy significantly reduces urban carbon emissions and enhances efficiency, a conclusion that remains valid after a series of robustness checks. Secondly, there is a notable structural effect, with different dimensions of the digital economy exhibiting varying impacts on urban emission reduction and efficiency enhancement. Thirdly, green economic efficiency and green technological innovation are crucial mechanisms through which the digital economy facilitates urban carbon emission reduction and efficiency improvement, operating through green development and innovation channels. Fourthly, industrial structure upgrading is a key nonlinear factor reducing the digital economy’s impact on carbon reduction, while the digital economy’s effect on urban carbon efficiency shows a U-shaped pattern. Lastly, the impact of the digital economy on urban carbon emissions displays significant heterogeneity across cities of different locations, tiers, and characteristics.